To divide the expression \( 56r - 12 \) by \( 4t \), we can break it down:
-
Separate the terms: \[ \frac{56r - 12}{4t} = \frac{56r}{4t} - \frac{12}{4t} \]
-
Simplify each term:
-
For \( \frac{56r}{4t} \): \[ \frac{56}{4} = 14 \quad \text{so} \quad \frac{56r}{4t} = \frac{14r}{t} \]
-
For \( \frac{12}{4t} \): \[ \frac{12}{4} = 3 \quad \text{so} \quad \frac{12}{4t} = \frac{3}{t} \]
-
-
Combine the simplified terms: \[ \frac{56r - 12}{4t} = \frac{14r}{t} - \frac{3}{t} \]
This can also be written as: \[ \frac{14r - 3}{t} \]
So the quotient when dividing \( 56r - 12 \) by \( 4t \) is: \[ \frac{14r - 3}{t} \]
The correct response among the options provided is: \[ \text{Start Fraction } 14 r - 3 \text{ over } t \text{ End Fraction} \]